Confucius Institute's effects on international travel to China: do cultural difference or institutional quality matter?. Issue 36 (2nd August 2017) - Lien, Donald; Yao, Feng; Zhang, Fan
ABSTRACT: This article uses a panel data of China's inbound tourist flows from 2005 to 2015 to investigate Confucius Institute (CI)'s influence on China's tourism. We find that CI, as a comprehensive platform for China's foreign cultural exchange, has a significant positive effect on China's tourist flows. The effects of CI on China's inbound tourism are transmitted through bridging cultural gaps and promoting Chinese language, which reduces psychic distance and transaction costs. CI also stimulates China's inbound tourist flows via reducing information asymmetry caused by different levels of institutional quality. Interestingly, we find that the heterogeneous effects of CI on China's inbound tourism depend on institutional quality, and the effects of CI to boost China's tourists are more prominent in departure countries with larger cultural difference.